e-Nelayan the Fishery Marketplace App - Mohammad Nazrul, Mornie; Nurfauza, Jali; Kartinah, Zen; Suriati Khartini, Jali (UNIMAS Publisher, 2021)
Smartphones have become an essential device that not only actsas a communication media, but it is also able to assist its user to do multiple tasks. A fisherman is an example of a community member that usesa smartphone. If a smartphone is fully utilised, it can be a huge help for the fishermen to sell their catch and fishery products. However, there is no proper medium, such as anmobile application,for this group of people to sell their catch. Hence, the e-Nelayan Marketplace App is introduced. This app enables the fishermen mainly in Kota Samarahan to sell their catch and other fishery products moreeffectively. The functionalities of this app include the ability to advertise the catch and let customersand fishmongersknow the type of fish being sold. In addition, an interactive graphical user interfacewas designed to display the output of each functional module. In order to evaluate the user acceptance towards the app, several tests were conducted, such as the performance, portability, compatibility, and usability testing. With the development of this project, it is hoped that the application willbenefit not only fishermen but also customers and fishmongers.